2017
DOI: 10.1017/s0142716417000388
|View full text |Cite
|
Sign up to set email alerts
|

In hand and in mind: Effects of gesture production and viewing on second language word learning

Abstract: To date, within the context of second language (L2) word learning, nonspontaneous representational gesture viewing's impact on memory and spontaneous gesture production's impact on communication have been examined separately. Thus, it is unclear whether and how these effects interact, particularly in the same individuals. The present study addresses this question by comparing these effects and by examining their influence on one another. To do so, a dialogic task was employed in which participants learned word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…One proposal for how gestures might come to have their facilitative effects for listeners is that seeing a speaker gesture activates a simulation of the gesture in the listeners' motor systems, or in some cases, encourages the listener to actually produce a similar gesture (e.g., Iani & Bucciarelli, 2017;Ping, Goldin-Meadow, & Beilock, 2014;Quandt, Marshall, Shipley, Beilock, & Goldin-Meadow, 2012). Indeed, seeing others' gestures prompts listeners to use similar gestures when they talk about the same topics (Child, Theakston, & Pika, 2014;Kimbara, 2006;Mol, Krahmer, Maes, & Swerts, 2012;Morett, 2018).…”
Section: Limitations Of the Gsa Frameworkmentioning
confidence: 99%
“…One proposal for how gestures might come to have their facilitative effects for listeners is that seeing a speaker gesture activates a simulation of the gesture in the listeners' motor systems, or in some cases, encourages the listener to actually produce a similar gesture (e.g., Iani & Bucciarelli, 2017;Ping, Goldin-Meadow, & Beilock, 2014;Quandt, Marshall, Shipley, Beilock, & Goldin-Meadow, 2012). Indeed, seeing others' gestures prompts listeners to use similar gestures when they talk about the same topics (Child, Theakston, & Pika, 2014;Kimbara, 2006;Mol, Krahmer, Maes, & Swerts, 2012;Morett, 2018).…”
Section: Limitations Of the Gsa Frameworkmentioning
confidence: 99%
“…Testing adult learners, Morett (2014Morett ( , 2018 obtained similar results and showed that gesture production facilitates L2 words (Hungarian) recall more effectively than gesture viewing. In sum, gesture-based benefits on memorizing linguistic materials occur both when participants perform the gestures themselves and also when they just observe the gestures produced by others (cf.…”
Section: Effects Of Gesture-based Enrichmentmentioning
confidence: 77%
“…Similarly, intervention studies have reported that using gestures helps vocabulary teaching (e.g. Kelly et al, 2009;Macedonia et al, 2011;Macedonia & Klimesch, 2014;Morett, 2018;Tellier, 2008), the teaching of tones and intonations (e.g. Morett & Chang, 2015;Yuan, González-Fuente, Baills, & Prieto, 2019), but not segmental phonology (e.g.…”
Section: Gesture and L2 Learningmentioning
confidence: 99%
“…If so, the participants should be able to understand the meaning or intention of recasts better when they are accompanied with gestures (2) A collection of gestural studies has shown that seeing the gestures that describe the meaning of the L2 vocabulary helps vocabulary learning (e.g. Kelly et al, 2009;Macedonia et al, 2011;Macedonia & Klimesch, 2014;Morett, 2018;Tellier, 2008). Then, seeing teachers' gestures that metaphorically explain the meaning of a grammatical function may help with L2 grammar learning.…”
Section: Limited Effects Of Gesture-enhanced Recast On Oral Production Test Of the Regular Past Tensementioning
confidence: 99%